The Effect of Financial Literacy, Financial Inclusion, and the Ability to Prepare Financial Statements on the Financial Performance of MSMEs in the Trade Sector in Pontianak - Sarwawan Hidayat; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of financial literacy, financial inclusion, and the ability to prepare financial statements on the financial performance of MSMEs in the trade sector in Pontianak City. This study employs a quantitative approach with an associative research design. The sampling technique used was purposive sampling, involving 150 MSME actors as respondents. Primary data were collected through the distribution of questionnaires using a five-point Likert scale and subsequently analyzed using multiple linear regression after passing validity tests, reliability tests, and classical assumption tests. The results of the analysis indicate that partially, financial literacy does not have a significant effect on the financial performance of MSMEs. In contrast, financial inclusion and the ability to prepare financial statements have a positive and significant effect on the financial performance of MSMEs. Simultaneously, financial literacy, financial inclusion, and the ability to prepare financial statements have a significant effect on the financial performance of MSMEs. The correlation coefficient (R) value of 0.758 indicates a strong relationship between the independent variables and the dependent variable, while the coefficient of determination (R²) value of 0.575 indicates that 57.5% of the variation in MSME financial performance can be explained by the three variables, while the remaining portion is influenced by other factors outside the research model. The findings of this study indicate that improvements in MSME financial performance do not solely depend on the level of financial knowledge, but are more strongly determined by access to formal financial services and technical capabilities in systematically preparing financial statements as a basis for business decision-making.